2023
DOI: 10.3390/polym15132882
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Tea Polyphenol in Zein through Complex Coacervation Technique to Control the Release of the Phenolic Compound from Gelatin–Zein Composite Film

Shabbir Ahammed,
Md Easdani,
Fei Liu
et al.

Abstract: Green tea polyphenol (TP) was encapsulated in zein and fabricated into a gelatin–zein composite film by complex coacervation. Transglutaminase (TG) crosslinking was employed to obtain a compact structural orientation of the film to prolong the release of bioactive compounds. The encapsulation efficiency of zein and the TP release rate from the composite film were investigated. The retention rate was over 30% and 80% after film fabrication and storage, respectively. Crosslinking decreased the diffusion coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This increase in the energy required to break the hydrogen bonds between Pec and Gel can also confirm the results of the XRD pattern, where it was also observed that increasing the concentration of Pec (T4 film) caused an increase in the degree of crystallinity of the structure. Many studies have observed similar changes with the addition of Pec and anthocyanin to the matrix of smart films ( Zheng et al, 2022 , Ahammed et al, 2023 , Lin et al, 2023 ).…”
Section: Resultsmentioning
confidence: 73%
“…This increase in the energy required to break the hydrogen bonds between Pec and Gel can also confirm the results of the XRD pattern, where it was also observed that increasing the concentration of Pec (T4 film) caused an increase in the degree of crystallinity of the structure. Many studies have observed similar changes with the addition of Pec and anthocyanin to the matrix of smart films ( Zheng et al, 2022 , Ahammed et al, 2023 , Lin et al, 2023 ).…”
Section: Resultsmentioning
confidence: 73%
“…Van Ballegooie et al modified zein with polyethylene glycol (PEG) to improve its stability ( 30 ). Ahammed et al used glutamine-transaminase (TG) modified gelatin-zein complex loaded with green tea polyphenols (TP) to control the release of phenolic compounds ( 31 ). In this experiment, we prepared nanoparticles to properly encapsulate and transport CBD by enhancing the flexibility of zein, facilitating its delivery of CBD to the small intestine for release and absorption.…”
Section: Introductionmentioning
confidence: 99%